Reynolds Syndrome: a rare rheumatologic disease that internists should have in mind. Case report - Jairo Morantes-Caballero; Nairo Cano-Arenas; Juan Francisco Rodríguez de Narváez (Case Reports)
Introduction. Reynolds syndrome (RS) is an autoimmune disorder characterized by overlapping primary biliary cirrhosis (PBC) and limited cutaneous systemic sclerosis (lcSSc). Some published cases do not report pulmonary arterial hypertension (PAH), and diagnoses are usually based on clinical, immunological and histological findings, mainly focused on dermatologic features, on those associated with Sjögren's syndrome, or on an interesting presentation of malignant thymoma; only one case of reported PAH was found, but it was an image report.